Medidas de espectroscopia Raman em cristais KDP e Nanotubos de Carbono: implementação da técnica - FERREIRA, Marcel Luiz Rodrigues (2008)
Currently, physicist have developed new techniques for characterization materials, mainly in the field of new materials that are being produced from existing materials such as glass, ceramics, polymers, semiconductor and superconductor materials, magnetic materials, etc. In that line, the Group of Physic of materials of Amazon has acquired new techniques for material characterization and this work is the beginning of the implantation of Raman spectroscopy technique. In this work, we used sample of KH2PO4 crystals (KDP) and carbon single wall nanotube (SWNT). The KDP was chosen because their spectra are well-known and their preparation quite simple. The KDP pure or doped is still researched due have a ferroelectric transition and their several applications in laser, sensors, second and third harmonic generation. SWNT was used in this work because are materials of great scientific and technological interest with applications in nanotechnology such as transistor, diode. KDP samples were submitted uniaxial pressure and high temperatures to investigated possible phase transition. Both decomposition and phase transition was observed through Raman spectra of KDP. In the SWNT Raman spectra was identified well known D and G bands. The results support implantation of Raman spectroscopy in the Laboratory of spectroscopy of UFPA.